Life stages and phylogenetic position of the wool carder bee mite Sennertionyx manicati (Acari: Acaridae) - Fan, Qing-Hai; Li, Dongmei; George, Sherly (Zootaxa, 2020)
In mites of the family Acaridae, usually two developmental stages, adult (males, females) and deutonymphal stage (=hypopus) are used for diagnostic descriptions. Because these taxonomically important stages live in different habitats (i.e. deutonymphs are phoretic on a hymenopteran host, while adults live inside the nest of the host), one of these can be missing or they cannot be confidently corelated with each other. Sennertionyx manicati (Acari: Acaridae) was only known from hypopus. Herein, we describe all post-embryonic stages of S. manicati based on material obtained from a nest of Anthidium manicatum in Auckland, New Zealand, and provide a key to all life stages of this species. We also conducted a phylogenetic analysis of the 18S gene and the D2/D3 region of 28S genes from field-collected specimens and GenBank data. The molecular analysis indicated the New Zealand specimen shared the identical 18S and 99.5% identity of the D2D3 region of 28S sequences with S. manicati from Italy, and clustered together in the phylogenetic trees.